The Role of Artificial Intelligence in Revolutionizing Online Gaming: Innovations, Challenges, and Future Prospects - Ravali Kandur, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The integration of Artificial Intelligence in online gaming has revolutionized the interactive entertainment landscape, transforming how games are developed, experienced, and evolved. This article examines the multifaceted impact of AI technologies across various aspects of gaming, from player experience systems to technical infrastructure. The article explores how AI-driven adaptive gameplay mechanisms, procedural content generation, and sophisticated NPC intelligence systems are reshaping player interactions and game development processes. The article investigation delves into the technical challenges and ethical considerations surrounding AI implementation in gaming, including security concerns, algorithm bias, and data protection. The article highlights the emergence of advanced development tools, optimization techniques, and performance enhancement systems that are fundamentally changing how games are created and maintained. Through analysis of current implementations and future trends, this article provides insights into how AI is not only enhancing gaming experiences but also opening new avenues for computational social science, education, and behavioral research in virtual environments.
Keywords: Artificial Intelligence in Gaming; Adaptive Gameplay Systems; Procedural Content Generation; Player Experience Modeling; Gaming Ethics and Security